Quantitative Analysis of Immunoglobulin E Reactivity Profiles in Patients Allergic or Sensitized to Natural Rubber Latex (Hevea Brasiliensis) - Raulf-Heimsoth, M (2016)
Characterized native and recombinant Hevea brasiliensis (rHev b) natural rubber latex (NRL) allergens are available to assess patient allergen sensitization profiles. OBJECTIVE: Quantification of individual IgE responses to the spectrum of documented NRL allergens and evaluation of cross-reactive carbohydrate determinants (CCDs) for more definitive diagnosis. METHODS: Sera of 104 healthcare workers (HCW; 51 German, 21 Portuguese, 32 American), 31 spina bifida patients (SB; 11 German, 20 Portuguese) and 10 Portuguese with multiple surgeries (MS) were analysed for allergen-specific IgE antibody (sIgE) to NRL, single Hev b allergens and CCDs with ImmunoCAP technology. RESULTS: In all patient groups rHev b 5-sIgE concentrations were the most pronounced. Hev b 2, 5, 6.01 and 13 were identified as the major allergens in HCW and combined with Hev b 1 and Hev b 3 in SB. In MS Hev b 1 displayed an intermediate relevance. Different sIgE antibody levels to native Hevea brasiliensis (nHev b) 2 and rHev b 6.01 allowed discrimination of SB with clinical relevant latex allergy vs. those with latex sensitization. Sensitization profiles of German, Portuguese and American patients were equivalent. rHev b 5, 6.01 and nHev b 13 combined detected 100% of the latex-allergic HCW and 80.1% of the SB. Only 8.3% of the sera showed sIgE response to CCDs. CONCLUSIONS: Hev b 1, 2, 5, 6.01 and 13 were identified as the major Hev b allergens and they should be present in standardized latex extracts and in vitro allergosorbents. CCDs are only of minor relevance in patients with clinical relevant latex allergy. Component-resolved diagnostic analyses for latex allergy set the stage for an allergen-directed immunotherapy strategy